2022
DOI: 10.19106/jmedsci005401202204
|View full text |Cite
|
Sign up to set email alerts
|

The significance of glycated haemoglobin, randomized admission blood glucose, and fasting blood glucose on in-hospital adverse cardiac events in patients with ST-elevation acute myocardial infarction

Abstract: In an ST-segment elevation acute myocardial infarction (STEMI), glucose metabolism undergoes disturbance secondary to acute myocardial injury, which affects the clinical outcome during the acute phase. Glucose metabolic disturbance indices are glycated haemoglobin, admission random glucose, and fasting glucose in blood circulation during STEMI. This is a retrospective cohort study, aimed to investigate whether glycated haemoglobin, admission random blood glucose, and fasting blood glucose levels are the risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…3 Our previous studies showed that in patients with acute hyperglycemia and diabetes mellitus, higher levels of blood glucose during AMI episodes increased the incidence of adverse cardiovascular events. 4,5 One mechanism that may explain the poorer prognosis is the enhanced platelet activation and subsequent thrombus formation. 6 Platelet-derived microparticles (PDMPs) play an important role in CVD, especially in atherosclerotic CVD.…”
Section: Introductionmentioning
confidence: 99%
“…3 Our previous studies showed that in patients with acute hyperglycemia and diabetes mellitus, higher levels of blood glucose during AMI episodes increased the incidence of adverse cardiovascular events. 4,5 One mechanism that may explain the poorer prognosis is the enhanced platelet activation and subsequent thrombus formation. 6 Platelet-derived microparticles (PDMPs) play an important role in CVD, especially in atherosclerotic CVD.…”
Section: Introductionmentioning
confidence: 99%